Religious freedom and inviolable lines in pluralist societies: the case of cultural crimes (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Multicultural societies and conflicts of loyalty: cultural crimes - 2. The Italian reaction to cultural crimes - 3. The case of kirpan: the recent judgment of the Court of Cassation - 4. A questionable decision: the fundamental role of pluralism in Western societies - 5. Conclusions: the centrality of human dignity.ABSTRACT: Pluralist societies pose new challenges to legal systems, having to find trade-offs between accommodating the necessities of minorities and security concerns. Religions often impose prescriptive rules on the behaviour of their believers, leading to moral internal conflicts when these lead to break State laws. In Italy, this subject was already discussed between legal scholars, before it received large public attention in 2017, where a judgement of the Cassation Court has upheld the conviction of a Sikh indian for withholding a kirpan, a ritual dagger central to his faith. This work provides an overview of the debate raised by the ruling, with particular emphasis on the challenges in devising policies that address security concerns without sacrificing religious freedom and pluralism. The Italian answer to cultural crimes will be analysed in depth, given the distinctive element of positive laicità in 1948 Constitution that characterizes its context. In the conclusion, a possible solution focused on human dignity is suggested.